Chemical Composition and Trypanocidal Activity of the Essential Oils from Hedychium coronarium J. Koenig (Zingiberaceae) - Rodrigues, Danilo Fernando [UNESP]; Arenas Velásquez, Angela María [UNESP]; Cavaleiro, Carlos; Salgueiro, Lígia; Martins, Gilmárcio Zimmermann [UNESP]; Magalhães, Nathália Oliveira [UNESP]; Martins, Maria Bernadete GonÇalves [UNESP]; Cicarelli, Regina Maria Barretto [UNESP]; Moreira, Raquel Regina Duarte [UNESP] (Hindawi, 2013)
The composition of the essential oils (EO) from leaves and rhizomes of Hedychium coronarium was analyzed both by gas chromatography and gas chromatography-mass spectroscopy. Thirty and thirty-nine compounds were identified, respectively, in the oils from leaves and rhizomes, representing 88% and 86.1% of the whole compositions. Caryophyllene oxide is the major component in rhizomes while 1,8-cineole predominates in leaves oil. Essential oils and major components were tested for trypanocidal activity using procyclic forms of Trypanosoma brucei (427 and 29-13 strains). The cytotoxicity index (CI50), using the MTT colorimetric method, showed that essential oils and 1,8-cineole were inactive (>100 μg·mL−1. Nevertheless, caryophyllene oxide revealed a remarkable activity against both T. brucei strains (CI50 = 65.77 μg·mL−1 and 24.53 μg·mL−1, resp.), and the synergism between caryophyllene oxide plus pentamidine (1 : 1, v/v) highly increased the trypanocidal activity (<1.0 μg·mL−1).
Keywords: chemical composition of essential oils; trypanocidal activity; Trypanosoma brucei